Synergy between Wayang Orang Ngesti Pandowo and higher education in supporting sustainable education program - Restu Lanjari Lanjari; Eny Kusumastuti; Utami Arsih (Jurnal Cakrawala Pendidikan, 2026)
This research examines the synergy between the Wayang Orang Ngesti Pandowo performing arts and higher education in supporting sustainable development (SDG 4), with a focus on integrating local wisdom to foster social cohesion among university students. As a cultural heritage form rich in moral values such as gotong royong, tolerance, and respect for tradition, Wayang Orang Ngesti Pandowo has excellent potential to build students’ social awareness and cultural identity. This research employs qualitative methods, utilizing data collection techniques such as in-depth interviews, observation, and document analysis, to explore how this performing art can be integrated into the higher education curriculum. The results showed that students’ involvement in Wayang Orang performances significantly increased their sense of community, social interaction, and understanding of local wisdom values while creating an inclusive learning environment. Students’ participation in the creative process, from rehearsal to performance, also positively impacted their communication, cooperation, and leadership skills. In addition, the collaboration between students and Wayang Orang artists strengthened social ties in the academic community and wider society. This research recommends that higher education institutions systematically integrate local wisdom-based performing arts into their curriculum through workshops, training, and collaboration with arts communities, as well as encouraging the government to support the preservation of local culture through educational policies. Thus, this research makes a significant contribution to the development of local culture-based education theory and practice, serving as a model for future similar initiatives that support social cohesion and sustainable education.